VAGINAL DELIVERY AFTER CAESAREAN SECTION - Ayub, Muhammad (Journal of Ayub Medical College Abbottabad, 2012)
The trend to deliver with caesarean section has increased in the recent years. The factors affecting this trend need re-consideration. Most of the women would deliver normally after a trial of labour after previous caesarean section. The obstetricians should abide by ethics in clinical practice, carefully evaluate the indication before every caesarean section, and take an unbiased decision before performing a caesarean section. Trend to deliver with caesarean section (CS) has increased recently. The underlying factors are increased knowledge, availability of facilities and patients' fear of vaginal birth. Many women are now opting for a caesarean delivery, even when it is not absolutely required. Moreover, some obstetricians find it easy to perform a CS rather than to wait longer in trial of labour. On the basis of the available evidence the concept of a prophylactic caesarean section being outrageous has been shattered by the fact that almost a third of female obstetricians would choose it for themselves.1 Increased rate of primary caesarean delivery in the United States in recent years, and a declining vaginal birth after caesarean (VBAC) rate has increased the overall rate of caesarean deliveries.2 Recent increases in the proportion of US women with a prior caesarean delivery mean that an increasing number of women are faced with the choice and associated risks of either VBAC or repeat caesarean delivery.3 A prior caesarean birth increases the risk of both elective and emergency caesarean births and uterine rupture in a subsequent pregnancy.4 A trial of labour after prior caesarean delivery is associated with a greater perinatal risk than is elective repeated caesarean delivery without labour, although absolute risks are low. This information is relevant for counselling women about their choices after a caesarean section.5 Women with a history of a prior caesarean birth may receive conflicting information regarding options in future pregnancies related to the choice of a trial of labour after a caesarean (TOLAC) or having an elective repeat caesarean delivery (ERCD).6 Need for induction and augmentation of labour are both factors associated with an increased likelihood of unsuccessful vaginal birth and risk of uterine rupture.4 Trial of labour after caesarean (TOLAC) delivery is currently a hot obstetrical topic owing to the acute rise in the rate of caesarean deliveries, both primary and repeat.7 Certain labour management practices increase the risk for uterine rupture 2-3 times, although the absolute increase is small from a baseline uterine rupture rate.8 After accounting for labour duration, induction is not associated with an increased risk of uterine rupture in women undergoing TOLAC.9 Ultrasonography can be a useful tool for evaluation of the uterus in planning a normal delivery after previous CS. Ultrasound measurements of the CS scar expressed as residual myometrial thickness (RMT) and the change in RMT between the first and the second trimester of pregnancy, can accurately predict a successful trial of labour in patients with one previous CS.10 To meet patient expectations for a safe and successful outcome with a trial of labour after caesarean delivery (TOLAC), specific management plans, checklists, practical coverage arrangements, and simulation drills are necessary.11 The reports Health Committee Maternity Services and Changing Childbirth suggested that women should have a pivotal role in their obstetric care. On the basis of the available evidence the concept of a prophylactic caesarean section being outrageous has been shattered by the fact that almost a third of female obstetricians would choose it for themselves.1 A motherto-be must be explained in detail the benefits and risks of a CS before she opts for or is made to accept the CS for delivery of her child. The obstetrician must neither simply be a technician to receive dictation from her patient, nor should be deciding herself alone about the mode of delivery. The option of CS should be left only for a really deserving case with genuine reasons for a primary or a subsequent CS, and not only because of a previous caesarean section. Excluding a small number of cases who require an elective CS, labour may safely be permitted in women who have had one previous caesarean section, and most will deliver vaginally.12 Induction of labour does not increase the risk of repeat caesarean section or uterine rupture. Though oxytocin may be administered to augment inefficient labour, the combined use of oxytocin to accelerate labour and analgesia significantly increases the risk of uterine rupture.12 Obstetricians should abide by ethics in clinical practice and carefully evaluate the indication in every CS and take an unbiased decision before performing CS on demand/request. Although the debate will continue regarding the appropriateness of CS on demand, any discussion of risks and benefits must include the J Ayub Med Coll Abbottabad 2012;24(1) 2 http://www.ayubmed.edu.pk/JAMC/24-1/Editorial.pdf potential for long term risks of repeated CS, including hysterectomy and maternal and foetal death.13